Communicating COVID-19 to rural dwellers: Revisiting the role of traditional media in crisis communication. (1st June 2021) - Abaneme, Ezinne; Nwasum, Chinedu; Chima, Oscar; Elechi, Ogbonnanya; Uduma, Ngozi
The recording of the index case of COVID-19 in Nigeria prompted the government to activate emergency communication strategies across the country. This study examines the awareness of the COVID-19 virus amongst rural dwellers and the importance of traditional media in health crisis communication amongst the residents of Ebonyi state. An adult sample size of 95 persons (32 male and 63 female) was assessed. The study adopts an in-depth interview as the research design. Data were generated using an interview guide and analysed thematically. The results show that rural dwellers are aware of the virus and the compliance level is high. There is a huge dependence on traditional media like town crier as the source of information amongst rural dwellers. The present study highlights the need to include rural dwellers in crisis communication planning and the integration of traditional media in future crisis communication planning.